The PML-Interacting Protein DAXX: Histone Loading Gets into the Picture - Salomoni, Paolo (Frontiers in Oncology, 2013)
The promyelocytic leukemia (PML) protein has been implicated in regulation of multiple key cellular functions, from transcription to calcium homeostasis. PML pleiotropic role is in part related to its ability to localize to both the nucleus and cytoplasm. In the nucleus, PML is known to regulate gene transcription, a role linked to its ability to associate with transcription factors as well as chromatin-remodelers. A new twist came from the discovery that the PML-interacting protein death-associated protein 6 (DAXX) acts as chaperone for the histone H3.3 variant. H3.3 is found enriched at active genes, centromeric heterochromatin, and telomeres, and has been proposed to act as important carrier of epigenetic information. Our recent work has implicated DAXX in regulation of H3.3 loading and transcription in the central nervous system (CNS). Remarkably, driver mutations in H3.3 and/or its loading machinery have been identified in brain cancer, thus suggesting a role for altered H3.3 function/deposition in CNS tumorigenesis. Aberrant H3.3 deposition may also play a role in leukemia pathogenesis, given DAXX role in PML-RARα-driven transformation and the identification of a DAXX missense mutation in acute myeloid leukemia. This review aims to critically discuss the existing literature and propose new avenues for investigation.